ANALISIS KUALITAS PELAYANAN DI PUSKESMAS NGALIYAN KOTA SEMARANG - Yuwono, Dhiarbima Adi; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Public service is a form of service provided by the Government to meet the needs of its people. The quality of public services is the primary feature of a service product provided by public service providers to the recipients of services. One form of a public organization that provides health services to the general public is Puskesmas (Community Health Center). Community Health Center as one of the PSA (Public Service Agency) is the spearhead in the development of public health. Ngaliyan Community Health Center is a functional organization which has the task in providing comprehensive and integrated service to the Ngaliyan community. The purposes of this study is to determine the quality of health services in Ngaliyan Semarang and also to know how to supporting and inhibiting aspects of service quality in Ngaliyan Community Health Center Semarang. There are several dimensions that are used to measure the quality of services provided by of Ngaliyan Community Health Center Semarang. These dimensions consist of tangible, empathy, reliability, responsiveness and assurance. The results of this research that the quality of services provided by of Health Center is not good enough. Because these are many aspects detan the services provided by Health Centers Semarang. Dimensions that are need to be improved to escalate the quality of services in the dimension is tangible, reliability and assurance. Because on these three dimensions, there are many efforts to improve the quality of service and it can be done with added numbers of employees, facilities and infrastructure and service time.